Review of Film Directing: Shot by Shot—25th Anniversary Edition: Visualizing from Concept to Screen - Elizabeth R. Berner (Journal of Applied Communications, 2023)
Review of Film Directing: Shot by Shot—25th Anniversary Edition: Visualizing from Concept to Screen.
Keywords: Videography; Directing; Storyboard